Exploring the Coordinated Development of Ecological Environment and Economy in Jiangxi Province, China - Yangcheng Hu, Tengteng Liu, Zhongyue Yan (Forest Chemicals Review, 1970)
This study constructed a set of indexes to evaluate the coordination levels of ecological environment and economy using entropy weight method and adopted the 11 cities of Jiangxi Province, China as a case. The results show that: (1) There was a general increasing trend in the levels of economic development of the 11 cities of Jiangxi from 2004 to 2018 characterized by low fluctuation, slow growth, and favorable stability. (2) The comprehensive evaluation of the ecological environment from 2004 to 2018 showed downward fluctuating trends followed by gradual upward trends with slow growth and poor stability. However, most cities have experienced decreasing levels of ecological environment in recent years. (3) The coordinated development of ecological environment and economy remained stable with rising fluctuations from 2004 to 2018. Although coupling moved toward a generally sound and coordinated state, several cities experienced downward trends. Coupling coordination levels also manifested as moderate imbalance, mild imbalance, imbalance, coordination, and basic coordination. The coupling coordination degrees of different cities were characterized by high-value-centered clustered development with a moderate coupling coordination degree and clear differences in spatial distribution. Meanwhile, the factors constraining coupling and coordinated developments of different cities included the lagging economy and the lagging ecological environment. The present study demonstrated that Jiangxi should adhere to the principles of green development, actively develop advantageous industries, and attach great importance to the governance of the ecological environment.